Development of a comparative fiqh supplement based on the 4D method to enhance understanding and tolerance attitudes - Hidayat, Saiful; Ahmad; Al Kattani, Abdul Hayyie (Tawazun: Jurnal Pendidikan Islam, 2026)
This study aims to develop a comparative Fiqh learning supplement for senior high school students as a solution to broaden their understanding of differing views among the four major Islamic schools of thought: Hanafi, Maliki, Shafi’i, and Hanbali. The research uses a Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The Define stage involves analyzing student needs and curriculum; Design focuses on creating the supplement according to learning standards; Develop tests the product feasibility through expert validation and limited trials; Disseminate is conducted on a limited scale. Validation results from experts indicate the supplement is highly feasible, with an average score of 84.6. Limited trials with senior high school students show very positive responses in terms of readability, attractiveness, and ease of understanding. This supplement is expected not only to enhance students’ comparative fiqh knowledge across madhhabs but also to foster tolerance, critical thinking skills, and maturity in addressing differences in Islamic law. Further research is recommended to test the product’s effectiveness on a larger scale and to develop more interactive learning media. Abstrak Penelitian ini bertujuan mengembangkan suplemen pembelajaran Fiqih Perbandingan untuk peserta didik Sekolah Menengah Atas sebagai solusi untuk memperluas wawasan terhadap perbedaan pandangan dalam empat madzhab utama Islam yaitu Hanafi, Maliki, Syafii, dan Hanbali. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model 4D (Define, Design, Develop, Disseminate). Tahap Define dilakukan dengan analisis kebutuhan peserta didik dan kurikulum; Design merancang suplemen sesuai standar pembelajaran; Develop menguji kelayakan produk melalui validasi ahli dan uji coba terbatas; Disseminate dilakukan dalam lingkup terbatas. Hasil validasi ahli menunjukkan bahwa produk suplemen sangat layak digunakan dengan skor rata-rata 84,6. Uji coba terbatas pada peserta didik SMA menunjukkan respons yang sangat positif, dan produk ini diharapkan dapat meningkatkan pemahaman komparatif fiqih madzhab, menumbuhkan sikap toleran, berpikir kritis, dan kedewasaan dalam menyikapi perbedaan. Penelitian ini merekomendasikan uji efektivitas produk secara lebih luas dan pengembangan media pembelajaran interaktif.